ZnAl-LDH@MXene modified by inhibitor as a nanofiller applied on Mg alloys coating protection. (February 2023) - Wu, Yulong; Wu, Liang; Yao, Wenhui; Chen, Yonghua; Zhou, Yan; Wang, Linqian; Wu, Ting; Jiang, Bin; Atrens, Andrej; Pan, Fusheng
Abstract: Recently, MXene/Epoxy coatings have attracted attention for its outstanding corrosion and wear resistance. However, the self-restacking tendency of MXene in epoxy resins affects the mechanical properties of coatings. Herein, ZnAl-LDH-NO3 - nanosheets were grown on MXene by one-step hydrothermal method to inhibit its spontaneous aggregation, and then the ZnAl-LDH-NO3 - @MXene mixed with epoxy resin was spun onto the pre-prepared Mg PEO coatings. ZnAl-LDH-NO3 - @MXene nanocomposite had long-term dispersibility, resulting in a satisfactory sealing of the Mg PEO coatings. The lowest wear rate and corrosion current density of the final coating demonstrated that LDH and MXene nanosheets presented a good synergistic effect. Moreover, nitrate was simultaneously intercalated into the guest layer of the ZnAl-LDH providing a self-healing function. This work proposed a new strategy to solve the self-restacking of MXene and facilitate its anticorrosion/wear applications in epoxy coatings: that is MXene-based nanocomposite. Graphical abstract: Image 1 Highlights: ZnAl-LDH carrying NO3 − was grown on Ti3 C2 nanosheets by one-step hydrothermal. The nanocomposite has a self-healing ability, giving a good sealing of PEO film. MXene and ZnAl-LDH have synergy effect to enhance anticorrosion/wear of coating.